Non-invasive imaging in dermatology and the unique potential of raster-scan optoacoustic mesoscopy - Hindelang, B.; Aguirre, Juan; Schwarz, M.; Berezhnoi, A.; Eyerich, K.; Ntziachristos, V.; Biedermann, Tilo; Darsow, U. (Journal of the European Academy of Dermatology and Venereology, 2019)
In recent years, several non-invasive imaging methods have been introduced to facilitate diagnostics and therapy monitoring in dermatology. The microscopic imaging methods are restricted in their penetration depth, while the mesoscopic methods probe deeper but provide only morphological, not functional, information. ‘Raster-scan optoacoustic mesoscopy’ (RSOM), an emerging new imaging technique, combines deep penetration with contrast based on light absorption, which provides morphological, molecular and functional information. Here, we compare the capabilities and limitations of currently available dermatological imaging methods and highlight the principles and unique abilities of RSOM. We illustrate the clinical potential of RSOM, in particular for non-invasive diagnosis and monitoring of inflammatory and oncological skin diseases.
CRIS-Team Scopus Importer:2023-03-08